TINJAUAN YURIDIS SENGKETA PEMBERHENTIAN H. ERISMAN, S.E SELAKU KETUA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KOTA PADANG OLEH GUBERNUR PROVINSI SUMATERA BARAT BERDASARKAN PERSPEKTIF SIYASAH DUSTURIYAH - Hendra Gunawan; Muhammad Afif (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
The main problem in this thesis is the dispute over the dismissal of H. Erisman, S.E as the chairman of the Regional Representative Council (DPRD) of Padang City by the Governor of West Sumatra Province from the perspective of siyasah dusturiyah. The purpose of this discussion is to Know and explain the chronology of the dismissal of H. Erisman, S.E as chairman of the Padang City Regional Representative Council (DPRD) by the Governor of the Province of West Sumatra, Knowing the formal aspects and material aspects of the dispute over the dismissal of H. Erisman, S.E as chairman of the Padang City Regional Representative Council (DPRD) by the Governor of West Sumatra Province in the Padang State Administrative Court, Knowing and explaining siyasah dusturiyah's view of the dispute over the dismissal of H. Erisman, S.E as the Chairman of the Regional People's Representative Council (DPRD) of Padang City by the Governor of West Sumatra Province.